STUDENT ENGAGEMENT AND ADOLESCENT MISBEHAVIOR: A CORRELATIONAL STUDY ON HIGH SCHOOL STUDENTS IN LUWU TIMUR - Tarmizi Thalib; Wuni Addawiyah; Nurhikmah Nurhikmah (JURNAL NALAR PENDIDIKAN, 2024)
This research aims to determine the relationship between student engagement and juvenile delinquency among SMA X students in East Luwu. The research sample consisted of 262 students aged 15-19 years. Data collection used the student engagement scale and juvenile delinquency scale. Pearson Product Moment was used for data analysis in this research with the help of the JASP 0.18.3 application. The research analysis results show a relationship between student engagement and juvenile delinquency at SMA X East Luwu with a correlation (r) -0.172 and p = 0.000, which means both variables have a relationship in a hostile and significant direction. This means that the higher student engagement, the lower juvenile delinquency. Conversely, the lower student engagement, the higher the rate of juvenile delinquency.